Answer:
Inverse property
Step-by-step explanation:
Answer:
3(a - b)(a + b)
Step-by-step explanation:
Factorize: (2a - b)² - (a - 2b)²
- Different of Perfect a Square rule: a² - b² = (a + b)(a - b)
(2a - b)² - (a - 2b)² = [(2a - b) + (a - 2b)] × [(2a - b) - (a - 2b)]
1. Distribute and Simplify:
Distribute the (+) sign on the first bracket and simplify: [(2a - b) + (a - 2b)] → 2a - b + a - 2b → (3a - 3b)
Distribute the (-) sign on the first bracket and simplify: [(2a - b) - (a - 2b)] → 2a - b – a + 2b → (a + b)
We now have:
(3a - 3b)(a + b)
2. Factor out the Greatest Common Factor (3) from 3a - 3b:
(3a - 3b) → 3(a - b)
3. Add "(a + b)" back into your factored expression:
3(a - b)(a + b)
Hope this helps!
<span>(4.214) x (3.06) = 12.89484 and can be rounded up to 12.9</span>
Answer:
I think the answer to your question is 19 seconds because if you do the math you get a vertex
Step-by-step explanation:
Using a calculator
Answer:
x = 18
Step-by-step explanation:
The parts of the triangles are proportional, so you can write ...
2x/80 = 27/60
Multiply by 120:
3x = 54
Divide by 3:
x = 18